Surgeon General's Call to Action to Improve Maternal Health in America. Issue 3 (May 2021) - Simpson, Kathleen Rice
Abstract : The Surgeon General's call to action to improve maternal health published in the last weeks of the previous administration is reviewed. There are numerous laudable goals and recommendations to promote safer care for mothers and babies in the United States.